IMPLEMENTASI GAYA KEPEMIMPINAN MENGGUNAKAN TIPE PATERNALISTIK DALAM MENINGKATKAN SUMBER DAYA MANUSIA - Melisa Srimurty Aprilia; Intan Alvionita; Misbahul Khoiri; Moch. Fanil Abrori; Yunita Amalia (Universitas Islam Darul Ulum Lamongan, 2021)
This study aims to support and study the role of leaders in improving Desa Bremi in social psychology. The style or style of a leader greatly influences his followers or subordinates. The type or style of a paternalistic leader is a leader who uses or applies to perceptions, values ​​held, attitudes and protections seen in needs. Desa bremi is a village located in District Krucil of Probolinggo Regency, East Java, which is expected to be able to provide quality human resources. As a leader in the village Bremi made efforts to be able to direct HR well from the problem of HR development. This study used a qualitative descriptive study using a sample technique of 4 respondents using interviews and observation and documentation. From this sample the researchers chose from the village apparatus, one RT / RW chairman and 2 villagers.